Anatomy of a storm: A review of shape analysis research that fuses form and function in weather forecasting and analysis. (February 2023) - Zick, Stephanie E.
Features in the natural and built environment can be viewed as objects, and an object's shape provides valuable information about the physical processes that generate those features. Formally, shape is defined as an object's characteristics independent of rotation, translation, and scale. Shape analysis involves quantification of an object's form. Shape metrics, or indices, are mathematical quantities that characterize the object's size and shape. Shape analysis has a rich history in geography and, more specifically, in meteorology and climatology research, with early examples in the identification of comma-shaped clouds in satellite imagery and "hook echoes" in radar reflectivity imagery. At its basis, shape analysis can be characterized as image analysis, which involves processing an image to extract meaningful information. Shape analysis usually involves image segmentation to isolate objects of interest and region analysis to calculate statistical data about these object(s). Current shape analysis research in meteorology and climatology can be split into two broad themes: (1) verification studies to compare model forecasts with observations and (2) process studies that provide information about the dynamical structure of a particular weather or climate phenomenon. In this report, I provide examples of emerging research that uses shape analysis to study tropical cyclones, mesoscale weather phenomena, and atmospheric rivers. Thus far, most of the process studies have been related to TC structure. Future research should also consider innovative approaches to image segmentation, new spatial verification methods for ensemble forecasting products, and more shaped-based process studies in mesoscale meteorology.